The London Exercise And Pregnant smokers (LEAP) trial: a randomised controlled trial of physical activity for smoking cessation in pregnancy with an economic evaluation. - Ussher, M; Lewis, S; Aveyard, P; Manyonda, I; West, R; Lewis, B; Marcus, B; Riaz, M; Taylor, A; Barton, P; Daley, A; Essex, H; et al. (NIHR Journals Library, 2015)
Smoking during pregnancy is the main preventable cause of poor birth outcomes. Improved methods are needed to help women to stop smoking during pregnancy. Pregnancy provides a compelling rationale for physical activity (PA) interventions as cessation medication is contraindicated or ineffective, and an effective PA intervention could be highly cost-effective.To examine the effectiveness and cost-effectiveness of a PA intervention plus standard behavioural support for smoking cessation relative to behavioural support alone for achieving smoking cessation at the end of pregnancy.Multicentre, two-group, pragmatic randomised controlled trial and economic evaluation with follow-up at the end of pregnancy and 6 months postnatally. Randomisation was stratified by centre and a computer-generated sequence was used to allocate participants using a 1 : 1 ratio.13 hospitals offering antenatal care in the UK.Women between 10 and 24 weeks' gestation smoking five or more cigarettes a day before pregnancy and one or more during pregnancy.Participants were randomised to behavioural support for smoking cessation (control) or behavioural support plus a PA intervention consisting of supervised treadmill exercise plus PA consultations. Neither participants nor researchers were blinded to treatment allocation.The primary outcome was self-reported, continuous smoking abstinence between a quit date and end of pregnancy, validated by expired carbon monoxide and/or salivary cotinine. Secondary outcomes were maternal weight, depression, birth outcomes, withdrawal symptoms and urges to smoke. The economic evaluation investigated the costs of the PA intervention compared with the control intervention.In total, 789 women were randomised (n = 394 PA, n = 395 control). Four were excluded post randomisation (two had been enrolled twice in sequential pregnancies and two were ineligible and randomised erroneously). The intention-to-treat analysis comprised 785 participants (n = 392 PA, n = 393 control). There was no significant difference in the rate of abstinence at the end of pregnancy between the PA group (7.7%) and the control group (6.4%) [odds ratio for PA group abstinence 1.21, 95% confidence interval (CI) 0.70 to 2.10]. For the PA group compared with the control group, there was a 33% (95% CI 14% to 56%), 28% (95% CI 7% to 52%) and 36% (95% CI 12% to 65%) significantly greater increase in self-reported minutes of moderate- and vigorous-intensity PA from baseline to 1 week, 4 weeks and 6 weeks respectively. Accelerometer data showed that there was no significant difference in PA levels between the groups. There were no significant differences between the groups for change in maternal weight, depression, withdrawal symptoms or urges to smoke. Adverse events and birth outcomes were similar between the groups except for there being significantly more caesarean births in the control group than in the PA group (28.7% vs. 21.3%; p < 0.023). The PA intervention was less costly than the control intervention by £35 per participant. This was mainly attributable to increased health-care usage in the control group. However, there was considerable statistical uncertainty around this estimate.During pregnancy, offering an intervention combining supervised exercise and PA counselling does not add to the effectiveness of behavioural support for smoking cessation. Only 10% of participants had PA levels accessed by accelerometer and it is, therefore, unclear whether or not the lack of an effect on the primary outcome is the result of insufficient increases in PA. Research is needed to identify the smoking populations most suitable for PA interventions and methods for increasing PA adherence.Current Controlled Trials ISRCTN48600346.This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 19, No. 84. See the NIHR Journals Library website for further project information.